2018
DOI: 10.1186/s12903-018-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of platelet-rich fibrin as a scaffold in regenerative endodontic treatment: a retrospective controlled cohort study

Abstract: BackgroundBlood Clot (BC) or platelet concentrates have been used as scaffold in regenerative endodontic treatment (RET). The aim of this retrospective study was to compare the performance of platelet-rich fibrin (PRF) with BC in inducing root development and periapical lesion healing after tooth revascularization.MethodsFive patients receiving RET using PRF as a scaffold were matched 1:1 to a previous cohort of 5 patients who underwent tooth revascularization by provoking periapical bleeding. Clinical signs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…29 On the other hand, Bezgin et al 25 did not found any significant difference for treatment outcomes between PRP and BC groups. In a randomized controlled study investigating the efficacy of PRF in RET cases, Ragab et al 39 reported that PRF might help to improve 36 consistently found no significant difference between PRF and BC groups in terms of clinical and radiographical outcomes. Ulusoy et al 38 compared RET protocols using PRP, PRF, platelet pellet, and BC and reported that all treatment groups had similar radiographic outcomes regarding the assessment of all root dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 On the other hand, Bezgin et al 25 did not found any significant difference for treatment outcomes between PRP and BC groups. In a randomized controlled study investigating the efficacy of PRF in RET cases, Ragab et al 39 reported that PRF might help to improve 36 consistently found no significant difference between PRF and BC groups in terms of clinical and radiographical outcomes. Ulusoy et al 38 compared RET protocols using PRP, PRF, platelet pellet, and BC and reported that all treatment groups had similar radiographic outcomes regarding the assessment of all root dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of them were excluded with reasons shown in the systematic flow chart (Figure 1). The general information and the study characteristics of the 18 included studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] are shown in detail in Table 2.…”
Section: Study Selectionmentioning
confidence: 99%
“…PRF is considered as an appropriate scaffold material and a promising tool for regenerative endodontics due to its ability to control differentiation of stem cells and deliver growth factors in sustained and controlled manner. Platelet rich plasma (PRP)/PRF combined with collagen membranes was used extensively for periodontal ligament and alveolar bone regeneration as guided tissue in periodontics and oral surgery [174].…”
Section: Endodontics: Platelet Rich Fibrin (Prf) For Pulp Regenerationmentioning
confidence: 99%
“…2,9 However, there is a limited number of cases in the literature in which PRF is used as a tissue scaffold. 9,11,[14][15][16][17][18] The purpose of this case series is to present the long-term follow-up of regenerative endodontic treatments using PRF tissue scaffold in four necrotic immature permanent teeth.…”
Section: Introductionmentioning
confidence: 99%